Analisis Implementasi Teknologi Informasi & Komunikasi (TIK) pada Pembelajaran Pendidikan Agama Islam di Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Ilyas Al Fath - Ahmad Rifai (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
This study aims to analyze the extent of the use of ICT in Islamic religious education learning, what are the obstacles and constraints faced and how the YouTube application contributes as an additional learning resource to the understanding of students. The method used in this study is a qualitative method. This research was conducted at MDTA Ilyas Al-Fath where students in grade 1 were the subjects of this study. The data collection method used observation, interviews and literature studies. The qualitative data analysis was carried out through the approach of data collection, data reduction, data presentation and drawing conclusions. The results of the study showed that the implementation of Information and Communication Technology (ICT), especially infocus, laptops, and the YouTube application in Islamic Religious Education learning at MDTA Ilyas Al-Fath has been effective. This is manifested in the implementation carried out through learning through videos of ablution procedures and prayer movements and readings that are implemented. Furthermore, the teachers directly teach students to do what they have seen to then be practiced in real life. The obstacles or constraints faced include the difficulty of teachers in managing student discipline, uneven knowledge of students and infrastructure conditions that are not yet fully adequate. Meanwhile, external obstacles include parents who are still less attentive and environmental conditions that affect the discipline of students in applying what they have learned. The implementation of ICT using the help of the YouTube application has produced real contributions. This can make it easier for teachers and students. In terms of making it easier for teachers because with the help of ICT, learning can be carried out efficiently so that it is possible to apply theoretically and practically to students.